Studies on the shootborer, Hypsipyla grandella (Zeller) (Lepidoptera: Pyralidae). XX. Observations on emergence and mating of adults in captivity - Sliwa, David; Becker, Victor O. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
This paper presents observations on the emergence and mating of Hypsipyla grandella in captivity. The average pupal stage lasted eight days. Pupal size elongated by 12 percent shortly before emergence. Emergence occurred most frequently in the evening hours when ambient light intensity was between 15 and zero lux. Adults emerged from the anterior part of the pupa and generally took approximately one minute to emerge. Wing expansion and drying lasted approximately 11 minutes. Adults remained nearly motionless during the day. General activity, including flight, walking, and antennal twirling by stationary newly emerged adults, began when ambient light intensity approached 10 lux. Females began to become sexually attractive five hours after zero lux and after little courtship behavior, mated between 6.5 and 10 hours after zero lux. Pairs remained together for approximately two hours.